Effect of Internal Audit Function on Audit Fees - Laras Auditria Putri; Muhammad Iqbal Ramadhan (Budapest International Research and Critics University, 2022)
This study aims to obtain effect of internal audit function on audit fees. The research approach uses a quantitative approach. The implementation of this research was carried out on All Companies except the Financial Sector listed on the Indonesia Stock Exchange in the period 2016 and 2017. The population of this study is All Companies except the Financial Sector listed on the Indonesia Stock Exchange in the period 2016 and 2017. The sampling is carry out purposive sampling. The data used in this study is secondary data. The analysis technique used is multiple linear regression with STATA software. The results of the study show that internal audit function, namely company size has a positive and significant effect on audit fees. Expertise of internal auditor has a positive and significant effect on audit fees. Internal certification has a positive and significant effect on audit fees.